Planar jumping with stable landing through foot orientation design and ankle joint control - Yuan, Qilong (2013)
This paper introduces a method to generate the planar jumping motion for biped robot. In this work, through determining the upper body posture trajectory in the flight phase, the foot landing posture is made to be flat while landing. Together with properly designing the trajectory for local center of gravity and the foot landing velocity, the soft landing trajectory is generated. A controller on the ankle joint is added to avoid significant impact with the ground and stabilize the robot after landing. Jumping motion with stable landing is achieved in a dynamic simulation environment based on this method.